A Mitochondria-Targeted Triphenylphosphonium-Conjugated Nitroxide Functions as a Radioprotector/Mitigator - Jiang, Jianfei (2009)
Removal of excessive mitochondrial reactive oxygen species by electron scavengers and antioxidants is a promising therapeutic strategy to reduce the detrimental effects of radiation exposure. Here we exploited triphenylphosphonium (TPP) cation as a means to target nitroxide radicals to mitochondria. We synthesized a library of TPP-conjugated nitroxides and tested their radioprotective effects in γ-irradiated mouse embryo cells and human epithelial BEAS-2B cells. Cells were incubated with conjugates either before or after irradiation. We found that [2-(1-oxyl-2,2,6,6-tetramethyl-piperidin-4-ylimino)-ethyl]-triphenyl-phosphonium (TPEY-Tempo) significantly blocked radiation-induced apoptosis as revealed by externalization of phosphatidylserine on the cell surface and inhibition of cytochrome c release from mitochondria. Using electron paramagnetic resonance, we showed that TPEY-Tempo was integrated into cells and mitochondria, where it underwent one-electron reduction to hydroxylamine. TPEY-Tempo acted as an electron scavenger that prevented superoxide generation and cardiolipin oxidation in mitochondria. Finally, TPEY-Tempo increased the clonogenic survival rate of irradiated cells. The cellular integration efficiencies of nonradioprotective TPP conjugates, including Mito-Tempo (Alexis, San Diego, CA), were markedly lower, although these homologues were integrated into isolated succinate-energized mitochondria to a similar extent as TPEY-Tempo. We conclude that mitochondrial targeting of TPP-conjugated nitroxides represents a promising approach for the development of novel radioprotectors.